<htm>Determinação do ciclo mitótico de dois cultivares de Gossypium hirsutum L. e dois ecótipos de Gossypium barbadense L. - Ferrer-Pereira, H. E.; Alcorcés-de-Guerra, N. C.; Méndez-Natera, J. R.; Alcorcés-de-Guerra, N. C. (Acta Biológica Paranaense, 2007)
Determinação do ciclo mitótico de dois cultivares de Gossypium hirsutum L. e dois ecótipos de Gossypium barbadense